2006
DOI: 10.5172/conu.2006.22.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Aboriginal peoples’ views of cancer in Australia

Abstract: Although the incidence of cancer in Indigenous peoples is similar to its incidence in the overall Australian population, Indigenous peoples are less likely to access early detection and medical interventions resulting in higher mortality and morbidity rates. To explore and address this discrepancy, the National Health and Medical Research Council funded a research study to examine Indigenous peoples' views of cancer and cancer treatments with an end goal of developing an innovative model of Indigenous Palliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 12 publications
1
85
1
Order By: Relevance
“…Research studies conducted in the Northern Territory and Western Australia that looked at the use of traditional medicine concluded Indigenous Australians do seek conventional medicine when ill but would also use traditional medicine if it were easier to access, particularly people who live in urban centres. 27,95,96 There are both similarities and differences in this study with other research findings on the use of traditional medicine. The study found Gumbi Gumbi was the most mentioned type of traditional medicine in all three communities.…”
Section: Influences On Health Care Decisionsmentioning
confidence: 65%
See 4 more Smart Citations
“…Research studies conducted in the Northern Territory and Western Australia that looked at the use of traditional medicine concluded Indigenous Australians do seek conventional medicine when ill but would also use traditional medicine if it were easier to access, particularly people who live in urban centres. 27,95,96 There are both similarities and differences in this study with other research findings on the use of traditional medicine. The study found Gumbi Gumbi was the most mentioned type of traditional medicine in all three communities.…”
Section: Influences On Health Care Decisionsmentioning
confidence: 65%
“…95 On analysing the quantitative and qualitative data some response patterns emerged. There was a small degree of consternation amongst peers regarding validity and generalisability because of the seemingly small sample size compared to population of the participating communities.…”
Section: The Ethics Approval Processes Involved Gatekeeper Support Frmentioning
confidence: 99%
See 3 more Smart Citations